Bridging the school-home divide in the middle grades: A process for strengthening school-family partnerships. Issue 1 (1st January 2018) - Kyzar, Kathleen; Jimerson, Jo Beth
Abstract: Evidence around adolescent learning and development is clear: School-family partnerships matter. However, traditional methods for engaging families that narrowly define who is involved and what constitutes involvement fall short of promoting optimal outcomes. Meaningful family engagement practices involve reciprocal, two-way interactions between educators and families. In this article, two scenarios illustrate how outreach and engagement efforts intersect with broader school cultures and the expectations of school leaders. The article outlines a three-phased process schoolwide teams can use to deepen understanding and implementation of family engagement practices to support adolescent learning and development. Embedded in the description of each phase are recommended readings, media, activities, and resources middle school teams can use to further professional learning on family engagement practices.